A treatment approach restoring esthetics in gingival recession in an anterior implant: A clinical report - Iffat Aara Shakir; Ponsekar A Abraham; M Vasanthakumar (Wolters Kluwer Medknow Publications, 2012)
This article details a technique to restore soft tissue esthetics in the anterior mandibular region following Zirconia implant therapy in a 40 year old male patient. The morbidity of gingival soft tissue and failure to adapt itself around the abutment lead to un-esthetic appearance in the anterior region. Gingiva coloured acrylic removable prosthesis was fabricated to replicate the gingival margin position and to achieve high esthetic results. This method may be considered a minimally invasive alternate treatment method for gingival soft tissue loss, providing esthetic results and patient satisfaction in a less time consuming manner.